Further insights in the ability of classical nonadditive potentials to model actinide ion–water interactions. Issue 9 (12th December 2012) - Réal, Florent; Trumm, Michael; Schimmelpfennig, Bernd; Masella, Michel; Vallet, Valérie
Abstract Pursuing our efforts on the development of accurate classical models to simulate radionuclides in complex environments (Réal et al., J. Phys. Chem. A 2010, 114, 15913; Trumm et al. J. Chem. Phys. 2012, 136, 044509), this article places a large emphasis on the discussion of the influence of models/parameters uncertainties on the computed structural, dynamical, and temporal properties. Two actinide test cases, trivalent curium and tetravalent thorium, have been studied with three different potential energy functions, which allow us to account for the polarization and charge‐transfer effects occurring in hydrated actinide ion systems. The first type of models considers only an additive energy term for modeling ion/water charge‐transfer effects, whereas the other two treat cooperative charge‐transfer interactions with two different analytical expressions. Model parameters are assigned to reproduce high‐level ab initio data concerning only hydrated ion species in gas phase. For the two types of cooperative charge‐transfer models, we define two sets of parameters allowing or not to cancel out possible errors inherent to the force field used to model water/water interactions at the ion vicinity. We define thus five different models to characterize the solvation of each ion. For both ions, our cooperative charge‐transfer models lead to close results in terms of structure in solution: the coordination number is included within 8 and 9, and the mean ion/water oxygen distances are 2.45 and 2.49 Å, respectively, for Th(IV) and Cm(III). © 2012 Wiley Periodicals, Inc.